Further Results for Encoding and Decoding Procedures of Asymmetric Low Magnitude Error Correcting Codes - Hamlet K. Khachatrian (Изд-во НАН РА)
In this paper an implementation of encoding and decoding procedures for double ±1 error correcting optimal linear codes over rings Z7 and Z9 is presented.
Keywords: Mathematics; Algorithm